2003
DOI: 10.1089/104303403321070865
|View full text |Cite
|
Sign up to set email alerts
|

High Cloning Capacity ofIn VitroPackaged SV40 Vectors with No SV40 Virus Sequences

Abstract: In vitro packaging of plasmid DNA using recombinant SV40 capsid proteins is a potentially useful procedure that overcomes some restrictions of the other SV40 systems such as the requirement for SV40 sequences and the limitation in size of DNA that can be packaged. The in vitro packaging system uses the four SV40 proteins (VP1, VP2, VP3, and agno) or VP1 only. The ability to confer drug resistance by three ABC transporter genes (MDR 1, MRP 1, or MXR) was determined using the surrogate fluorescent substrates rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…Moreover, it does not require any SV40 sequence, thus providing efficient gene delivery at the same level of safety when using nonviral vectors. [11][12][13] In this study, we demonstrate delivery of PE38 toxin with or without a combination of the chemotherapeutic agent doxorubicin. SV40 pseudovirion delivery of PE was found to be effective in the treatment of human adenocarcinomas growing in mice, either by direct injection or systemically.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it does not require any SV40 sequence, thus providing efficient gene delivery at the same level of safety when using nonviral vectors. [11][12][13] In this study, we demonstrate delivery of PE38 toxin with or without a combination of the chemotherapeutic agent doxorubicin. SV40 pseudovirion delivery of PE was found to be effective in the treatment of human adenocarcinomas growing in mice, either by direct injection or systemically.…”
Section: Introductionmentioning
confidence: 97%
“…These VLPs are composed of 90 dimers of the virus coat protein arranged in a T=3 symmetry; they are stable at low pH and to lyophilization, and easily produced and purified in large quantities using the baculovirus expression system [14]. The VLP vaccine stimulated systemic and mucosal immune response when administered orally in mice [8] and humoral, mucosal and cellular immune response in human volunteers [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly attractive is their use in transporting viral vectors for gene therapy and DNA vaccines, exploiting in some cases the natural tropism of the viral particles. It has been reported that supercoiled plasmid DNA up to 17 kb was encapsidated in vitro inside simian virus 40 capsid proteins [15] and that the HPV-16 L1 VLPs are able to package unrelated plasmid DNA in vitro and then to deliver this foreign DNA to eukaryotic cells with the consequent expression of the encoded gene. The gene transfer rate observed was higher than DNA delivered alone or with liposome [16].…”
Section: Introductionmentioning
confidence: 99%
“…SV40 ST is also encoded by this construct. Although there do not appear to be major size constraints to DNA packaging into SV40 particles in vitro (Kimchi-Sarfaty et al, 2003), an effort was made to keep the GFP recombinant close to the size of WT SV40. The genome of SV40vGFP is only 90 nucleotides smaller than the WT viral DNA.…”
Section: Sv40vgfp Cloningmentioning
confidence: 99%